The Top 10 Things a Beginning Health and Physical Education Teacher Needs to Know. (2nd January 2023) - Grube, Dan; Little, Stephanie; Stringer, Amy
Abstract: Beginning and experienced teachers were surveyed on the most important things a beginning health and physical education teacher (HPE) needs to know. The results showed a range of broad topics that affect early career teachers as they are inducted in to the teaching field. Some of the responses are more prescient and relate to current events and others relate to the new generation of teachers in the field. And some responses seem to address important aspects of teaching that are consistent with what we know about HPE curriculum and pedagogy and that continue to need strengthening in the ever-evolving landscape of education. The "top 10" list ranges from personal well-being to strategies for instruction and appropriate practices. Additionally, more current issues being addressed in schools such as the focus on relationships and culturally responsive teaching are reflected in the list. Finally, classroom management rose to the top and is reflective of something many teachers struggle with early in their careers